2014
DOI: 10.1002/pds.3729
|View full text |Cite
|
Sign up to set email alerts
|

The identification of incident cancers in UK primary care databases: a systematic review

Abstract: In UK primary care database studies, methods for identifying breast, colorectal, and prostate cancers were often unclear. Code lists were often unavailable, and where provided, we observed variation in the individual codes and types of codes included. Clearer reporting of methods and publication of code lists would improve transparency and reproducibility of studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…However, given that the main purpose of health administrative databases was initially to regulate health reimbursement, the definition of overall incident cancer needs a well‐defined algorithm to avoid the misclassification of new cancer cases. Still, a recent systematic review showed that many previous studies involving the UK primary database lacked transparency in defining cancer outcomes . The presence of a cancer code only may be insufficient to address cancer incidence because it may rely on follow‐up examination after cancer treatment, screening examination, personal or familial history of cancer or prophylactic surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that the main purpose of health administrative databases was initially to regulate health reimbursement, the definition of overall incident cancer needs a well‐defined algorithm to avoid the misclassification of new cancer cases. Still, a recent systematic review showed that many previous studies involving the UK primary database lacked transparency in defining cancer outcomes . The presence of a cancer code only may be insufficient to address cancer incidence because it may rely on follow‐up examination after cancer treatment, screening examination, personal or familial history of cancer or prophylactic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Still, a recent systematic review showed that many previous studies involving the UK primary database lacked transparency in defining cancer outcomes. 2 The presence of a cancer code only may be insufficient to address cancer incidence because it may rely on follow-up examination after cancer treatment, screening examination, personal or familial history of cancer or prophylactic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The capture of cancer cases in primary care electronic medical records, such as the General Practitioner Online Database, the primary care part of the Clinical Practice Research Datalink (known as CPRD), has been shown to be incomplete and to vary by cancer type. 1 3 …”
mentioning
confidence: 99%
“…The sensitivity, specificity and positive predictive values (PPV) of these algorithms varied considerably and depended not only on the specific cancer site, but also on the complexity of the algorithm used [ 10 ]. Moreover, a systematic review including 84 studies published between 1980 and 2013 showed that most researchers built their own algorithms to identify incident breast, prostate and colorectal cancer cases in primary care databases without, however, giving detailed explanations regarding their methods used [ 11 ].…”
Section: Introductionmentioning
confidence: 99%